Political Economy of Reform - Khemani, Stuti (World Bank, Washington, DC, 2017)
This paper reviews the literature relevant to understanding political constraints to economic reforms. Reform refers to changes in government policies or institutional rules because status quo policies and institutions are not working well to achieve the goals of economic well-being and development. Further, reforms refer to the alternative policies and institutions that are available that would most likely perform better than the status quo. The main question examined in the political economy of reform literature has been why reforms are not undertaken when they are needed for the good of society. The succinct answer from the first generation of research is that conflict of interest between organized socio-political groups is responsible for some groups being able to stall reforms so that they can extract greater private rents from status quo policies. The next generation of research is tackling a more fundamental question: why does conflict of interest persist; or, why do some interest groups exert influence against reforms if there are indeed large gains to be had for society? These are questions about norms and preferences in society for public goods. The next step is to examine where norms and preferences for public goods come from, and which institutional arrangements are more conducive to solve the public goods problem of pursuing reforms. After reviewing the available and future directions for research, the paper concludes with what all of this means for policy makers who are interested in understanding the factors behind successful reforms.